Core/shell Fe3O4/Gd2O3 nanocubes as T1–T2 dual modal MRI contrast agents. Issue 25 (14th June 2016) - Li, Fenfen; Zhi, Debo; Luo, Yufeng; Zhang, Jiqian; Nan, Xiang; Zhang, Yunjiao; Zhou, Wei; Qiu, Bensheng; Wen, Longping; Liang, Gaolin
Abstract : Core/shell Fe3 O4 /Gd2 O3 nanocubes and their application as T 1 – T 2 dual modal contrast agents for MR imaging in vivo . Abstract : T 1 – T 2 dual modal magnetic resonance imaging (MRI) has attracted considerable interest because it offers complementary diagnostic information, leading to more precise diagnosis. To date, a number of nanostructures have been reported as T 1 – T 2 dual modal MR contrast agents (CAs). However, hybrids of nanocubes with both iron and gadolinium (Gd) elements as T 1 – T 2 dual modal CAs have not been reported. Herein, we report the synthesis of novel core/shell Fe3 O4 /Gd2 O3 nanocubes as T 1 – T 2 dual-modal CAs and their application for enhanced T 1 – T 2 MR imaging of rat livers. A relaxivity study at 1.5 T indicated that our Fe3 O4 /Gd2 O3 nanocubes have an r 1 value of 45.24 mM −1 s −1 and an r 2 value of 186.51 mM −1 s −1, which were about two folds of those of Gd2 O3 nanoparticles and Fe3 O4 nanocubes, respectively. In vivo MR imaging of rats showed both T 1 -positive and T 2 -negative contrast enhancements in the livers. We envision that our Fe3 O4 /Gd2 O3 nanocubes could be applied as T 1 – T 2 dual modal MR CAs for a wide range of theranostic applications in the near future.